Peripheral Nerve Block Compared to Intra-Articular Injection for Post-Operative Pain Control in Total Ankle Arthroplasty: A Randomized, Controlled, and Non-Inferiority Trial. Issue 1 (January 2022) - Strasser, Nicholas L.; Bremer, Michelle; Owen, Erin C.
Category: Ankle Arthritis; Ankle; Other Introduction/Purpose: Ankle arthritis is associated with debilitating pain and chronic disability. Total ankle arthroplasty (TAA) is increasingly performed to treat end-stage arthritis resulting in favorable clinical outcomes. Peripheral nerve blocks (PNB) are widely used for post-operative pain management; however, PNB can lead to post-operative neuropathic complications. Intra- articular injections (IAI) have been widely reported as an alternative to PNB in total knee arthroplasty, resulting in lower post- operative narcotic consumption and accelerated functional recovery. Little information exists on patient outcomes following IAI in TAA. The purpose of this study was to assess the effectiveness and tolerability of IAI compared to PNB for pain control, measured by oral morphine milligram equivalents (MME) and a Visual Analogue Pain Scale (VAS), following TAA. Methods: We conducted a prospective, randomized, non-inferiority study involving 51 opioid naïve adults undergoing primary, unilateral TAA. Participants were randomized to IAI joint cocktail containing anesthetic and steroid at the completion of the TAA (n=26), injected in four joint capsule locations, or PNB (n=25). PNB included a single popliteal fossa block of the sciatic nerve and adductor canal block of the distal femoral nerve. Primary outcomes were mean difference in oral post-operative MME, via inpatient record and patient daily narcotic diaries, and post-operative pain measured by the VAS (0-100mm) at 24 hours and 2 weeks post-TAA. IAI was considered non-inferior to PNB if mean difference in consumption of narcotics was less than 30 MME (24 hour) and 75 MME (2 weeks), and the mean difference in pain was less than 15mm on the VAS using the upper limit of one- sided 95% confidence intervals (UCI) for increase in MME and VAS scores. Results: There were 39 patients with complete data. Mean oral MME in 24 hours was 50.4 (sd = 38.1) in the IAI group (n=22) versus 52.9 (sd = 48.1) in PNB (n=17) with -2.4 MME mean difference (UCI 20.8). Mean VAS at 24 hours was 25.6 (sd = 25.1) in IAI compared to 25.4 (sd = 29.2) in PNB. Mean difference in VAS at 24 hours was 0.22 (UCI 14.9). Mean two week post- VAS was 13.3 (sd = 17.2) in IAI compared to 15.1 (sd = 21.2) for PNB with mean difference of -1.8 (UCI 8.5). All demonstrate non- inferiority. At two week post- IAI reported 384.6 MME (sd = 491.0) and PNB 319.2 (sd = 323.7) with 65.5 MME difference (UCI 303.6), not supporting non-inferiority. Conclusion: IAI is non-inferior to PNB in the first 24 hours after TAA as measured by oral narcotic consumption and patient-self reported pain. At two week post-TAA, IAI resulted in non-inferior pain scores; however, non-inferiority was not confirmed for oral narcotic consumption due to the high variability in documented use. This study suggests IAI is effective for controlling immediate post-operative pain without introducing the neuropathic complications associated with PNB.